Autonomous mobile robots in unknown outdoor environments - Zhu, Xiaorui; Kim, Youngshik; Minor, Mark Andrew; Qiu, Chunxin (CRC Press, Taylor & Francis Group, 2018)
Mobile robots have been increasingly applied in many different scenarios, such as space exploration and search and rescue, where the robots are required to travel over uneven terrain while outdoors. This book provides a new framework and the related algorithms for designing autonomous mobile robotic systems in such unknown outdoor environments.